Teaching Assistance of Merdeka Belajar Kampus Merdeka Program of the Islamic Education Study Program of Lamongan Islamic University - Fathurrahman, Fathurrahman; Mumtahana, Lusia (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
The aim of writing this article is to analyze and describe MBKM teaching assistance at MAN 1 Lamongan. This research uses a qualitative descriptive case study. The focus of this discussion is to explain the teaching assistance for students of the Islamic religious education study program at the Lamongan Islamic University MBKM program which was carried out at MAN 1 Lamongan and was attended by 6 students. Research data was obtained through interview, observation, and documentation techniques as well as using a data analysis process: collection, reduction, and concluding. The research results show that there are three stages that students participating in teaching assistance go through. The preparation stage includes a briefing on the concept of teaching assistance, student functions and tasks, reflection, and planning for teaching assistance. The next implementation stage includes acceptance and observation, making teaching plans, implementing teaching, conducting assessments, and reflecting on closing the program. The final stage is analysis and results, including analysis of attitude competence, knowledge competence, teaching competence, general competence of the school environment, and evaluation of the entire activity program. In teaching assistance activities carried out at MAN 1 Lamongan, students gain new experiences that can shape their character to become good and professional teacher candidates.